2004
DOI: 10.1016/j.devcel.2004.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin Regulates Enamel Patterning in Mouse Incisors by Asymmetrically Inhibiting BMP Signaling and Ameloblast Differentiation

Abstract: Rodent incisors are covered by enamel only on their labial side. This asymmetric distribution of enamel is instrumental to making the cutting edge sharp. Enamel matrix is secreted by ameloblasts derived from dental epithelium. Here we show that overexpression of follistatin in the dental epithelium inhibits ameloblast differentiation in transgenic mouse incisors, whereas in follistatin knockout mice, ameloblasts differentiate ectopically on the lingual enamel-free surface. Consistent with this, in wild-type mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
211
0
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(227 citation statements)
references
References 45 publications
4
211
0
12
Order By: Relevance
“…BMP Signaling Has Been Shown to Induce Ameloblast Differentiation (15). We found Bmp4 and Bmp7 expression to be specifically downregulated in ameloblasts of Lrp4 hypo/hypo mutants at birth whereas expression was unaltered in odontoblasts ( Fig.…”
Section: Resultsmentioning
confidence: 69%
“…BMP Signaling Has Been Shown to Induce Ameloblast Differentiation (15). We found Bmp4 and Bmp7 expression to be specifically downregulated in ameloblasts of Lrp4 hypo/hypo mutants at birth whereas expression was unaltered in odontoblasts ( Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Numerous reports using gene targeting have shown that ablating function of BMP antagonists [Ectodin (Sostdc1, Wise) (49), Noggin (50), Osr2 (20)] increases tooth number. Similarly, ectopic expression of the BMP antagonist Follistatin, using the K14 promoter, reduces tooth number (51). BMP data for mammalian taste papillae are complicated and stage-specific.…”
Section: Discussionmentioning
confidence: 99%
“…The signals from the mesenchyme involved in the ameloblast induction include Bmp2, Bmp4, and Tgfb1 (Fig. 4) (Coin et al 1999;Wang et al 2004). In addition, Shh from the epithelial stratum intermedium cells is required to support ameloblast differentiation and maturation (Dassule et al 2000;Gritli-Linde et al 2002).…”
Section: Signaling Network Regulating Tooth Developmentmentioning
confidence: 99%